2020
DOI: 10.3389/fmed.2020.00487
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging in Psoriatic Arthritis: What Have We Learnt in the Last Five Years?

Abstract: Psoriatic arthritis (PsA) is a complex heterogeneous disease with multiple inter-related pathologies such as synovitis, enthesitis, tendinopathy, and dactylitis. Clinical assessment is limited in its detail to assess pathology, thus in recent years, ultrasound (US) has become more popular, given its high sensitivity to detect inflammatory arthritis and ability to inform clinical decisions. Although a qualitative technique, US findings can be graded semi-quantitatively for grayscale (GS) and power Doppler (PD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…This fact gives rise to the possibility that some subclinical synovitis were not detected. We consider this as a possible limitation of this study since some studies showed that SpA patients can have subclinical synovitis [47]. On the other hand, we had patients with PD signal grade 2 and 3, which is uncommon or absent in healthy subjects or in patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…This fact gives rise to the possibility that some subclinical synovitis were not detected. We consider this as a possible limitation of this study since some studies showed that SpA patients can have subclinical synovitis [47]. On the other hand, we had patients with PD signal grade 2 and 3, which is uncommon or absent in healthy subjects or in patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…Although less common and less intense, and seen in fewer joints, even power Doppler (PD) signal suggestive of subclinical synovitis is present in up to 55% of healthy subjects. 7 In the study by Ji et al, 8 there was no difference between RA and non-RA groups in terms of BME, either. The location and extent of BME may help in the differential diagnosis.…”
Section: General Overview Of Imaging Features and Modalitiesmentioning
confidence: 90%
“…Despite some research indicating PsA-specific lesions, further studies are needed to identify more specific features providing differentiation between inflammation-related enthesitis from metabolic, age-and overload-driven enthesopathy. 7,22 A further preliminary enthesitis score developed in a recent GRAPPA study has reported the ability to differentiate between PsA and healthy controls. 23 Among rheumatic diseases, RA and PsA may be especially difficult to differentiate.…”
Section: Update In Ultrasoundmentioning
confidence: 99%
“…Accumulating evidence is enhancing the role of ultrasonography as a useful, low-cost non-invasive technique to identify diagnostic features of EHOA and PsA [20,[30][31][32][33]. US, in fact, is able to visualize discontinuity of bone surface, joint space narrowing and osteoproliferation.…”
Section: Oa Erosive Arthritis and Dip Psa Similar Imaging Featuresmentioning
confidence: 99%
“…The high sensitivity of ultrasound technique to detect inflammatory signals [32,34] made this methodology able to provide detailed information also regarding PsA activity and features, as with US it has been possible to identify synovitis since subclinical stage [33]. Doppler may finally be used to identify specific features of PsA such as enthesitis and dactylitis [33] (Figure 3). Further imaging modalities provide reliable results in detection of typical lesions of both HEOA and PsA and help to make accurate diagnosis, as proved in clinical trials [35].…”
Section: Oa Erosive Arthritis and Dip Psa Similar Imaging Featuresmentioning
confidence: 99%